Ecological Attributes of Carnivore-Livestock Conflict - Ugarte, Carolina S.; Moreira-Arce, Darío; Simonetti, Javier A. (Frontiers in Ecology and Evolution, 2019)
Mitigation of carnivore-human conflict due to domestic animal predation represents an imperative challenge. Although livestock management strategies aimed at reducing predation have recently received attention by wildlife managers and producers, the information regarding ecological attributes of studied predators and environmental characteristics of the areas where conflicts occur is largely missing. We conducted a global review to characterize the literature of carnivore-livestock conflict, identifying the set of reported predators, and assessing the ecological attributes of these species and areas where predation has occurred. A total of 391 published peer-reviewed research papers on carnivore-livestock conflict containing 783 predation study cases were evaluated. Carnivore-livestock conflict research was largely conducted in Asian and African countries (80% of published studies). Fifty-two carnivores were reported in conflict-related studies being Felidae and Canidae the most frequently studied groups (80% of study cases). Carnivores more often reported to prey on domestic animals exhibit larger home ranges and body masses, and are also subject to larger reductions in their distribution ranges. They also show a generalist habitat behavior, a strictly carnivore diet, and cathemeral activity. Predation of domestic animals consistently increased with vegetation cover, decreased with distance from human settlement and was higher in young animals. The analysis conducted separately for large and meso carnivores showed that predation on domestic animals by large carnivores (> 21.5 kg) increased near protected areas and far from human settlements. Current information regarding conflicts exhibits a notable variation in research effort towards some regions and large-bodied and broadly distributed species. This asymmetry could reflect the role of human perspectives in research based on species-level traits, research facilities and funding opportunities, though also underlies ecological processes induced by land transformation occurring in some regions across the globe. As encroached habitat increases, species with restricted distributions and behaviors, or smaller home ranges such as meso carnivores, will roam into human-dominated landscapes, increasing their probability of interacting with livestock activity. Identifying ecological attributes that distinguish carnivores and areas as “conflict-prone” may contribute to set evidence-based management approaches in frameworks ready to anticipate, reduce or prevent human-carnivore conflict, complementing the use of other strategies.